Substratos alternativos para produção de mudas de espécies florestais da família Anacardiaceae nativas da caatinga - Nascimento, Augusto Vinicius de Souza (2022)
The Caatinga is an exclusively Brazilian biome, which occupies about 11% of the national area. One of the most striking features of this biome is its high degree of floristic endemism, which is seriously threatened by human activities, such as illegal deforestation to produce stakes, fence posts, firewood and charcoal, as well as the conversion of natural areas into plantations of large crops and pastures, putting several species of this biome at risk of extinction. In this context, up to 50% of the Caatinga is already altered in some way and the loss of vegetation cover drastically compromises the biodiversity of this biome. One of the botanical families present in the Caatinga is the Anacardiaceae, which is formed by approximately 81 genera and 800 species. Among the native forest species of the Anacardiaceae family occurring in the Caatinga, we can highlight Astronium urundeuva (M. Allemão) Engl. (aroeira-do-sertão), Spondias tuberosa Arruda (umbuzeiro) and Schinopsis brasiliensis Engl. (barauna). Considering the great socioeconomic and environmental importance that these species have for the Brazilian semiarid region, mainly due to their multiple uses, they have been exploited in an essentially extractive way, which has resulted in a decrease in their natural populations and loss of genetic variability. The objective of this work was to evaluate the feasibility of using alternative substrates for the production of seedlings of native forest species of the Anacardiaceae family. The use of bovine manure is efficient for the production of seedlings of baraúna and aroeira-do-sertão, increasing most of the analyzed variables, being able to be used in proportions between 10 and 40% of this residue. For umbuzeiro the use of cattle and sheep manure in the proportion of 10% is efficient to increase the initial growth of the seedlings. Urban sewage sludge can be used in proportions of 5 to 20% for the production of aroeira-do-sertão seedlings, increasing height, stem diameter and biomass accumulation. The use of alternative substrates is feasible for seedling production of forest species of the Anacardiaceae family, having the potential to be used as a substitute for commercial substrates.